Teacher Educators in K-12 Classrooms: How To Nurture Professional Development and Research - Taylan, Didem Rukiye; Tunç, Pekkan Zelha; Aydın, Utkun; Birgili, Bengi; Taylan, Rukiye Didem; Tunç-Pekkan, Zelha (North American Business Press, 2022)
Four mathematics teacher educators taught 5th grade mathematics for one year at a disadvantaged public school in a metropolitan city in Turkey. Teacher educators (TE) met every week for 10 months where they discussed what to teach, how to teach and reflected on implementation of their shared planning (Regular Meetings). In some meetings, there was a special focus on teaching and learning of fractions (Fraction Research Meetings). Videotapes of the first six Regular Meetings and six of the Fraction Research Meetings were analyzed. The focus of qualitative analyses was on how the pedagogical content knowledge (PCK) was constructed during meetings. References evidencing TEs' knowledge of students, instructional strategies and assessment were revealed more frequently during the Fraction Research Meetings compared to the Regular Meetings. Findings showed that TEs were more focused on what questions to ask in the classroom and shared their experiences about students' mathematical thinking more frequently. Framing planning and reflection discussions with a focus on conducting research was a productive way of nurturing professional development for TEs. Copyright of Journal of Higher Education Theory & Practice is the property of North American Business Press Inc. and its content may not be copied or emailed to multiple sites or posted to a listserv without the copyright holder's express written permission. However, users may print, download, or email articles for individual use. This abstract may be abridged. No warranty is given about the accuracy of the copy. Users should refer to the original published version of the material for the full abstract.
Keywords: Pedagogical content knowledge; Teaching experience; Mathematics; Teacher educators; Professional development